2018
DOI: 10.1093/annonc/mdy121
|View full text |Cite
|
Sign up to set email alerts
|

Alectinib versus chemotherapy in crizotinib-pretreated anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer: results from the phase III ALUR study

Abstract: BackgroundThis is the first trial to directly compare efficacy and safety of alectinib versus standard chemotherapy in advanced/metastatic anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancer (NSCLC) patients who have progressed on, or were intolerant to, crizotinib.Patients and methodsALUR (MO29750; NCT02604342) was a randomized, multicenter, open-label, phase III trial of alectinib versus chemotherapy in advanced/metastatic ALK-positive NSCLC patients previously treated with platinum-based do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
201
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(226 citation statements)
references
References 13 publications
7
201
1
6
Order By: Relevance
“…Some clinical trials have demonstrated that there is good efficacy of second generation ALK‐TKI in comparison to chemotherapy for crizotinib‐pretreated ALK‐positive NSCLC patients . In addition, some studies showed the remarkable efficacy of next generation ALK‐TKI tailored to the secondary mutation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical trials have demonstrated that there is good efficacy of second generation ALK‐TKI in comparison to chemotherapy for crizotinib‐pretreated ALK‐positive NSCLC patients . In addition, some studies showed the remarkable efficacy of next generation ALK‐TKI tailored to the secondary mutation .…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of crizotinib, a first generation ALK‐tyrosine kinase inhibitor (ALK‐TKI), to standard chemotherapy has been demonstrated in patients with ALK‐positive advanced NSCLC previously treated with platinum‐based chemotherapy . Sequentially, next generation ALK‐TKIs, such as alectinib, ceritinib, brigatinib and lorlatinib, have shown remarkable clinical efficacy in ALK‐positive NSCLC . However, even if patients initially respond well to ALK‐TKI, the majority eventually experience disease progression due to various mechanisms, including secondary mutations within the ALK tyrosine kinase domain and activation of alternative signaling pathways …”
Section: Introductionmentioning
confidence: 99%
“…According to the updated results, the median PFS for alectinib in first-line treatment was 34.8 months which was almost three times longer than the standard first-line treatment for ALK rearrangement [89]. Besides, the phase III ALUR study directly compared alectinib with chemotherapy in crizotinib-pretreated ALK-positive non-small cell lung cancer [111]. Median PFS was 9.6 months with alectinib and 1.4 months with chemotherapy as second-line treatment indicating an absolute clinical role of alectinib as a first-line setting.…”
Section: Alectinibmentioning
confidence: 99%
“…The mean duration of second-line treatment was set at 50.1 weeks, irrespective of the nature of the treatment. This value corresponds to the mean values of the duration of PFS reported in clinical trials evaluating the use of alectinib [16], crizotinib [17] and ceritinib [17]. Third-line treatment was considered to be followed from the end of second-line treatment until the patient died (or until the end of the ten-year modelling period).…”
Section: Model Inputsmentioning
confidence: 99%